Effect of the dry and rainy weather on the Idared and Golden Reinders apple varieties fruit quality - Illés, Attila; Nagy, Péter Tamás; Lang, Tamás; Szabó, Zoltán; Nyéki, József; Soltész, Miklós (Acta Agraria Debreceniensis, 2010)
Weather conditions have an important role in fruit production. In the last few decades, this role is increased and basically determines the fruit quality and quantity. Despite of this statement, there is but very few information about impacts caused by weather anomalies in Hungarian orchards. Regarding this, the relation between the external, and internal values of the Idared and Golden Reinders apple varieties, the changing of the temperature and precipitation in a dry year (2009) as well as in a rainy year (2010) were investigated. The examined apple varieties are grown at the same training system (rootstock, spacing, training, pruning system). The average weight, average diameter, acid content and soluble solids were higher in 2009 than in 2010, although the precipitation was higher in 2010. Due to the many rainy days the intensity of sunshine and the number of sunny days were less. To produce better quality it is very important the amount of the sunshine and heat, the optimal temperature and the precipitation rate.